Fertilizer Measuring Machine for Hydroponic Growing Industry - Tan Yhe Huan, Nathalie; bin Roslan, Hazli; binti Sari, Suhaila (Progress in Engineering Application and Technology, 2023)
In this era of globalization, most of the telecommunication systems in the industry are based on IOT. For a fertigation system that uses manual fertilizing methods, it has disadvantages such as requiring a large number of workers and delays in fertilizing due to the problem of delays in fertilizing by workers. In the fertigation plant method, the fertilizer mixture ratio and fertilization time are the main factors in making plant growth to the maximum and best level. Errors in the fertilizer mixture ratio and delay in fertilizing will result in damaged plant growth and consequently causing serious losses to plant operators in terms of fertigation. To prevent this problem from happening, a tool was developed and applied. The ratio of fertilizer measurements can be provided accurately and appropriately according to the level of plant growth. Fertilizer mixture A and B are measured in tanks separately with the same ratio before being mixed in the mixer tank. These fertilizers are measured using a TDS (Total Dissolved Solids) sensor and the optimum level of reading is around 400ppm to 550ppm. The available measured fertilizer will be pumped to the plants. To ensure that the soil moisture level, temperature and air humidity are always in the right range make sure that the plants are always in optimum situation, an application (Blynk) is applied and can work via Wi-Fi for the monitoring process using a mobile phone. This system is equipped with several other equipment such as a water level sensor as a gauge of the height of fertilizer and water, a water pump to pump fertilizer, an LCD display as a system monitoring display and an Arduino Mega as a controller for the entire system. This system works well based on the test results and data that has been taken during the testing process and is suitable to be applied to the fertigation farming system.